SISTEM TIKET HELPDESK PADA STMIK BANI SALEH - Zaenal Mutaqin Subekti; Kresno Murti Prabowo; Budi . (STMIK Dian Cipta Cendikia Kotabumi, 2022)
reporting problems related to personal computer (PC) damage, intranet or internet network troubles, requesting data on databases, and developing information systems. reporting of problems is still conventional by using the telephone for complaints or coming directly to the puskom/ukisi unit (main computer unit and information system) to provide information on problems or problems, if there is no urgent work, the carving team can immediately solve the problem, so there is no recording of damage or trouble reporting or data requests. The helpdesk ticket system for the stmik Bani Saleh uses method stages starting from requirements, design, implementation, and testing. It is hoped that the implementation of the helpdesk ticket system can make it easier to recap reports on repair work that has been carried out by the carving team, and can be analyzed for damage or problems that often occur